Criança: Fumante Passivo sem Opção - Lefèvre, Fernando; Cavalcanti Lefèvre, Ana Maria; M. T. Bicudo Pereira, Isabel; T. M. Stewien, Glacilda; P. Mirra, Antonio; Guaraciaba dos Santos Oliveira, Neusa; Cavalcanti Simioni, Ana Paula; de Medeiros, Ivany Yara (BEPA. Boletim Epidemiológico Paulista, 2004)